2014
DOI: 10.2214/ajr.13.12185
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guidelines for Imaging and Reporting Ingested Foreign Bodies

Abstract: The characteristics of foreign bodies and predisposing bowel abnormalities affect the decision to follow ingested objects radiographically, perform additional imaging, or proceed with endoscopic or surgical removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
141
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 83 publications
0
141
0
8
Order By: Relevance
“…Ingestion of foreign materials most commonly occurs in the pediatric population younger than 6 years of age or in adults 25 to 44 years of age, predominantly in males [6,7]. Malliwal et al [10] reported a 54-year-old male with a history of personality disorder who swallowed five AA batteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingestion of foreign materials most commonly occurs in the pediatric population younger than 6 years of age or in adults 25 to 44 years of age, predominantly in males [6,7]. Malliwal et al [10] reported a 54-year-old male with a history of personality disorder who swallowed five AA batteries.…”
Section: Discussionmentioning
confidence: 99%
“…Patients present to the emergency room mostly with symptoms of epigastric pain, dysphagia and chest pain. Onethird of patients are reported to be asymptomatic [6]. If an ingested foreign object is radiopaque, it is often detected and readily diagnosed by plain radiography [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Chest radiograph can be normal given most aspirated foreign bodies are radiolucent. Examples of radiolucent foreign bodies include food particles, some bones, wood, plastic, and thin metallic fragments.…”
Section: Wvmj Oamentioning
confidence: 99%
“…Examples of radiolucent foreign bodies include food particles, some bones, wood, plastic, and thin metallic fragments. 6,7 Hyperinflation, obstructive emphysema, rib flaring, and flattening of the ipsilateral hemidiaphragm are radiographic findings more commonly seen in children due to increased compliance of airways and ballvalve mechanism (On inspiration, bronchi expands and air can get past the foreign body. With expiration, the airway collapses around the foreign body, leading to trapping of air in distal lung).…”
Section: Wvmj Oamentioning
confidence: 99%